OBTAINING AND DETERMINATION OF IMMUNOGENIC PROPERTIES OF TRX-PD-1 RECOMBINANT PROTEIN - Adish , Zh.; Mukantaev, K.N.; Tursunov , K.A.; Kaukabayeva , G.K.; Kanaev , D.B.; Ramankulov, Ye.M.; Mukanov , K.K. (Eurasian Journal of Applied Biotechnology, 2019)
Monoclonal antibodies against programmed cell death receptor PD-1 are of particular interest for immunotherapy and blocking control points for tumor development. The PD-1 T-cell receptor is a regulator capable of inhibiting or completely suppressing the immune response. One of the important stages of obtaining monoclonal antibody is the immunization of BALB/c mice, the scheme of which depends on the nature of the antigen and its immunogenicity. The gene of PD-1 was synthesized by a two-step polymerase chain reaction using the Phusion High-Fidelity DNA Polymerase. The resulting construction based on the pET32 vector was transformed by electroporation into the E. coli BL21 expression strain, which resulted in the E. coli strain BL21/pET32/Trx-PD-1. Molecular weight of the protein Trx-PD-1 was 34 kDa. Western blot demonstrated presence of a hexahistidine tag in a protein with a molecular mass of 34 kDa. The highest antibody titers were observed in mice immunized with recombinant protein at a concentration of 100 μg/ml. Western blot revealed a specific reaction of PD-1 protein without thioredoxin with sera from immunized mice. The resulting construct pET32/PD-1 provided a high level of expression of the recombinant Trx-PD-1. The recombinant Trx-PD-1 induced high titers of antibody and stimulated B-lymphocytes.